BEMLAB2D: GUI MODELING, VISUALIZATION AND ANALYSIS WITH BOUNDARY ELEMENT ”“ AN APPLICATION INELASTOSTATIC PROBLEMS (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Abstract. The graphical user interface (GUI) in usual engineering problems, has facilitated the modeling as well as provides greater flexibility in meshing, boundary conditions and physical properties by employing visual tools, improving the analysis interpretation. However, with the need for more efficient computational implementations - less computational effort and shorter analysis, the boundary element method (BEM) comes as efficient and flexible suggestion, allowing greater versatility to the geometric modeling and meshing programs. The BEM stands out among the other numerical methods due todiscretization criterion of the model adopted, in the case it occurs only on the boundary thereof, making simple and versatile implementation. In this context, this work proposes the development of a graphical interface program easy user handling for pre-processing, calledBEMLAB2D and implemented in MATLAB for two-dimensional models analysis with BEM, which allows modelling complex geometries, including multiple regions , cracks and holes, as well as editing and viewing the results in an interactive and visual way.Keywords: GUI, Boundary Element Method, Elastostatic, Matlab, two-dimensional models.